2007
DOI: 10.1088/1748-6041/2/1/s09
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicates and biphasic HA-TCP composites: studies of properties for bony filling

Abstract: Aluminosilicate materials synthesized at room temperature present good mechanical properties. Hydroxyapatite, tricalcium phosphate or both offer a high biocompatibility in the biomedical field. In this work, we focused on the composites resulting from associations of these materials. The best compromise between porosity and biomechanical properties versus different parameters was determined. The in vitro behaviour of compounds in contact with the simulated body fluid (SBF) was studied and in vivo experiments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Aluminosilicate systems synthesised at room temperature by sol-gel route present attractive properties for medical application as biomaterials [1][2][3], but also as catalysts [4,5]. In addition to chemical composition, the structure, surface topographical features and the nanoscale changes in surface layer all have significant effects on their bioactive and catalytic properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminosilicate systems synthesised at room temperature by sol-gel route present attractive properties for medical application as biomaterials [1][2][3], but also as catalysts [4,5]. In addition to chemical composition, the structure, surface topographical features and the nanoscale changes in surface layer all have significant effects on their bioactive and catalytic properties [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminosilicate ceramic is a biomedical material that has shown biocompatibility in simulated body fluid. It is applied in bone filling, protein absorption, and nanobiocomposites [7][8][9][10]. The sol-gel dry spinning [11] technique has been extensively used for the fabrication of highly pure, homogeneous, crack-free aluminosilicate ceramic microfibers at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…reported that they successfully made materials which were accepted by host bone and provided good mechanical properties. Further, neither inflammation or encapsulation of the surrounding tissue occurred nor leaching out of harmful elements from the sample was recorded [3].…”
Section: Current State Of Artmentioning
confidence: 98%
“…Geopolymers are presently used for a variety of applications including heat resistant materials and fire protection. Specialist geopolymers have been developed as biomaterials to replace/ repair damaged animal bones [3] [4].…”
mentioning
confidence: 99%